Accelerated peripheral nerve repair using surface-modified biomaterials for targeted capture of glial-derived growth factors post-neurorrhaphy - Shiu-Jau Chen; Chih-Ming Lin; Chiung-Hui Liu; Yin-Hsiu Chen; Yu-Lin Hsieh; You-Cheng Lin; Yin-Hung Chu; Chung-Yao Ku; Wei-Li Liao; Wen-Chieh Liao (PLoS ONE, 2025)
Peripheral nerve injury (PNI) commonly leads to motor or sensory dysfunction, with nerve grafts being the standard treatment for neurorrhaphy. Despite advancements in biomaterials for nerve-tissue engineering, the rate of nerve regeneration remains slow. Therefore, this study aims to improve further the understanding of the impact of syndecan-3 (SDC3)-modified small intestine submucosa (SIS) on nerve reconstruction by employing two advanced approaches: cation recruitment and local growth factor delivery. Immunofluorescence staining confirmed the presence of SDC3 conjugated on the SIS. The enzyme-linked immunosorbent assay measured sustained glial cell line-derived neurotrophic factor (GDNF) levels in the SDC3-coated SIS. In vitro studies showed that SDC3-coated SIS retained GDNF in a dose-dependent manner, significantly enhancing Schwann cell proliferation compared with basal conditions. RSC96 cells proliferated most effectively on SDC3-coated SIS loaded with GDNF, and neuro-2A neurites were significantly longer on this material at 48 hours. One-month post-neurorrhaphy, morphological analysis revealed a 1.6 ±  0.02-fold increase in the number of β3-tubulin-positive axons in the GDNF+SDC3-coated SIS group compared to the SIS group. CMAP amplitude increases in the GDNF+SDC3-coated SIS group as more functioning motor axons are connected to the target muscle of ESN rats. This study provides valuable insights into the development of customized SDC3-coated SIS for promoting nerve tissue regeneration and accelerating rehabilitation.